Zum jüdischen Erbe in der Wiener Architektur : Der Beitrag jüdischer ArchitektInnen am Wiener Baugeschehen 1868-1938 (German) - Prokop, Ursula (Böhlau, 2016)
A survey of the role played by jewish architects working in Vienna in the period between 1868-1938.